2023
DOI: 10.1136/bmjopen-2022-069239
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impacts of COVID-19 on Vietnamese health workers over the prolonged restricted COVID-19 responses: a cross-sectional study

Abstract: ObjectiveWe assessed the psychological impact posed by COVID-19 and its associated factors on the healthcare workforce nationwide during the peak of Vietnam’s fourth outbreak.DesignA cross-sectional study.SettingOur study was conducted in 61 provinces of Vietnam.MethodsA total of 2814 healthcare professionals in 61/63 provinces of Vietnam. An online questionnaire using Patient Health Questionnaire-9 (PHQ-9), Perceived Stress Scale-4 (PSS-4) and Generalised Anxiety Disorder-7 (GAD-7) scales was distributed rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…For example, a recent meta-analysis found that approximately 33% of healthcare workers reported depressive symptoms, 42% exhibited anxiety features; approximately 40% experienced acute stress and 32% exhibited post-traumatic symptoms [ 2 ]. Our results were also lower than a prior online survey which showed that 49.7% of healthcare professionals (49.7%) had mild depressive symptoms [ 11 ]. However, findings in this study aligned with a previous study in two healthcare facilities, which indicated that the prevalence of stress, anxiety and depression in the first wave of COVID-19 was 8.0%, 17.5% and 14.8%, respectively [ 16 ].…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…For example, a recent meta-analysis found that approximately 33% of healthcare workers reported depressive symptoms, 42% exhibited anxiety features; approximately 40% experienced acute stress and 32% exhibited post-traumatic symptoms [ 2 ]. Our results were also lower than a prior online survey which showed that 49.7% of healthcare professionals (49.7%) had mild depressive symptoms [ 11 ]. However, findings in this study aligned with a previous study in two healthcare facilities, which indicated that the prevalence of stress, anxiety and depression in the first wave of COVID-19 was 8.0%, 17.5% and 14.8%, respectively [ 16 ].…”
Section: Discussioncontrasting
confidence: 97%
“…The scores for Depression, Anxiety, and Stress are calculated by summing the scores of the corresponding sub-categories and then multiplying the total by a factor of 2. Depression stratification entails five distinct levels: normal (0-9), mild (10)(11)(12)(13), moderate (14-20), severe (21-27), and very severe (28 and above). Anxiety is categorized into five levels, specifically normal (0-7), mild (8-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and very severe (20 and above).…”
Section: Predictor Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The total score ranges from 0 to 21, with higher scores indicating more severe anxiety symptoms. The validity and reliability of this scale have been assessed within the Vietnamese population including cancer patients 3,30 . This study used a cut‐off level of 10, with sensitivity (89%) and specificity (82%) 31 …”
Section: Methodsmentioning
confidence: 99%